Adipocere Inside Nineteenth Century Femora: The Effect of Grave Conditions. (7th October 2013) - Henderson, C. Y.; King, G. A.; Caffell, A. C.; Allen, R.
Abstract: Adipocere has, infrequently, been reported from archaeological contexts normally on the external surface of bodies. In contrast to those cases, this study focuses on a white, powdery and greasy substance found inside two right human femora during sampling. These samples were obtained from two identified individuals buried in the late 19th century, who were exhumed from a rock‐cut and a brick‐lined grave in a steeply sloping graveyard with wet soil conditions. Both individuals were buried in coffins. Fourier transform infrared spectroscopy was used to test the composition of the substances, and both were found to conform to the spectrum of adipocere. This is likely to be a breakdown product of the fats in bone marrow in an anaerobic, moist environment mediated by bacteria. None of the other individuals ( n = 6) buried in similar graves displayed evidence of adipocere; this includes those whose femora were in a similar state of preservation ( n = 4). Contemporaneous data on precipitation for the month of burials do not highlight any obvious trends, but one of the individuals was found in a water‐logged grave. The similar preservation of other femora buried in brick‐lined graves highlights the interplay of multiple factors in the formation and degradation of adipocere. More importantly, it demonstrates differential preservation, which may impact on DNA and other biomolecular research. Furthermore, this adds to the limited data currently available on adipocere found in archaeological contexts. Copyright © 2013 John Wiley & Sons, Ltd.